New information on the genetic cost of chicken domestication in Africa and Asia - CGIAR Research Program on Livestock (2021)
The research conducted reveals a new landscape of demographic history and genomic changes associated with chicken domestication and provides insight into the evolutionary genomic profiles of domesticated animals managed under modern human selection.